Establishment of a new approach for quality evaluation of Pseudobulbus Cremastrae seu Pleiones (Shancigu) based on multicomponent analysis and anti-liver cancer pharmacological effects - Yuxin Cao; Zhuangzhuang Hao; Mengmeng Liu; Jingwen Xue; Yuqing Wang; Tingyue Jiang; Ge Zhang; Wenxin Fan; ChunGuo Wang; Jinli Shi (Frontiers in Pharmacology)
BackgroundPseudobulbus Cremastrae seu Pleiones (Shancigu), a traditional Chinese medicine (TCM), has been extensively used in clinical practice for the treatment of various tumors, particularly liver cancer. Shancigu is classified into two commercial specifications—“Maocigu” and “Bingqiuzi”—which exhibit significant differences in appearance, chemical composition, and price, posing challenges for the quality control of medicinal materials.PurposeThe aim of this study was to clarify the quality evaluation indicators based on the anti-liver cancer active components in Shancigu and to establish a reliable quality evaluation method to preliminarily assess the quality of Shancigu from different commercial specifications and production areas.MethodsTwenty-six batches of Shancigu samples were collected. High-performance liquid chromatography (HPLC) was used to establish fingerprint spectra. In vitro anti-liver cancer pharmacological effect indicators were analyzed using the CCK-8 assay and scratch wound healing assays. Through spectrum–effect relationship analysis, serum pharmacochemistry analysis, and in vitro/in vivo anti-liver cancer activity evaluation, the effective component combinations of Bingqiuzi and Maocigu were identified and validated. Gray relational analysis (GRA) and the technique for order preference by similarity to ideal solution (TOPSIS) were subsequently applied to assess the quality of Shancigu based on their different specifications and origins.ResultsEleven key anti-liver cancer active components from Shancigu were screened and confirmed, namely, malic acid, citric acid, 2-isobutylmalic acid, gastrodin, batatasin III, 2-p-hydroxybenzyl-5,3′-dihydroxy-3-methoxybibenzyl, coelonin, 1-p-hydroxybenzyl-2,7-dihydroxy-4-methoxyphenanthrene, blestriarene A, blestriarene B, and monbarbatain A. These components are present in Bingqiuzi and Maocigu in different proportions, and the anti-liver cancer pharmacological effects of the effective component combinations were found to be equivalent to those of the original materials, both in vitro and in vivo. These 11 components can be used as indicators for evaluating the quality of Shancigu. Quality evaluations revealed no significant differences between Bingqiuzi and Maocigu. For Bingqiuzi, medicinal materials produced in Guizhou and Yunnan were of better quality; for Maocigu, those from Guizhou and Sichuan were superior.ConclusionIn this study, we established quality evaluation criteria for Shancigu and developed an innovative method to comprehensively assess the quality of Shancigu from different commercial specifications and production regions. By integrating component analysis with anti-liver cancer activity assessment, this research provides a valuable reference for the quality evaluation of other Chinese medicinal materials.